2021
DOI: 10.18280/isi.260303
|View full text |Cite
|
Sign up to set email alerts
|

E-SIP: Website-Based Scheduling Information System to Increase the Effectivity of Lecturer's Performance and Learning Process

Abstract: The development of internet and information technology made a system to the practical, effective, and efficient. One of the impacts is ease to make scheduling information system in university. This research is research and development (R&D) models which have aim to develop the website-based scheduling information system to increase the effectivity of lecturer’s performance and learning process in IAIN Tulungagung. E-SIP program develop by using software development life cycle in term of waterfall model. Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The identification of approaches for shaping online learning, class schedules, and organizational culture was based on a comparison of various literature sources. Anam et al (2021) indicated that internet development contributes to the formation of a practical, effective and efficient learning system, as well as facilitates easier process of creating schedules in the university. To this end, they developed the E-SIP program, which included the stages of needs analysis, design, testing, maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of approaches for shaping online learning, class schedules, and organizational culture was based on a comparison of various literature sources. Anam et al (2021) indicated that internet development contributes to the formation of a practical, effective and efficient learning system, as well as facilitates easier process of creating schedules in the university. To this end, they developed the E-SIP program, which included the stages of needs analysis, design, testing, maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Website-based applications run using internet and a browser [29]. Web-based applications are now becoming increasingly popular because of the interface that can be adapted to the user's needs and can be a medium of user communication [30].…”
Section: Website-based Final Project Management Designmentioning
confidence: 99%
“…Predicting college students' learning requirements is an important research aspect in the mobile education management field [1][2][3][4][5][6]. Because mobile learning is a personalized and continuous training method which is free from the limitations of time and space, so it's particularly important to make accurate predictions and good plans for college students' requirements for mobile learning [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%